Prevalência de antigenemia criptocócica em pessoas com Aids em um hospital de referência em Goiânia, Goiás - Borges, Moara Alves Santa Bárbara (2019)
Introduction: Cryptococcosis is caused by Cryptococcus species complex (Cryptococcus neoformans and Cryptococcus gattii) and targets immunocompromised individuals, including those with AIDS. Cryptococcal antigen (CrAg) detection in the HIV population with CD4 counts <100-200 cells/μL has been recommended by the World Health Organization since 2011 in areas with CrAg prevalence >3%. Objectives: To estimate the prevalence and to evaluate associated factors to CrAg positivity in AIDS population in Goiás, Midwest of Brazil. Methodology: A cross-sectional study, which evaluated HIV-infected adults, with a CD4 T-cell count <200 cells / μL, without previous history of cryptococcosis, regardless of the use of antiretroviral therapy (ART), time of diagnosis or symptoms, attended at a infectious diseases reference hospital in Goiânia, Goiás, from June 2015 to July 2018. Demographic, clinical and laboratory characteristics were investigated through interviews with the participants and review of medical records. The serum CrAg test was performed by the Lateral Flow Assay technique (Immuno-Mycologics Inc®, Norman, Oklahoma). The prevalence of cryptococcal antigenemia with Confidence Interval of 95% (95% CI) was estimated. Chi-square test or Fisher's exact test was used to compare categorical variables and T-test for continuous variables. The level of significance was set at p <0.05. Results: Of the 214 individuals recruited, 72% were men ranging in age from 18 to 78 years (median, 40 years). HIV diagnosis was recent in 47% (≤12 months) and 88.8% (n=190) were antiretroviral experienced, of which 51.4% (n=110) were taking this regularly in the previous 3 months. Viral load was undetectable in 25/214. CD4 values ranged from 1 to 199 cells/μL (median, 47 cells/μL). The overall prevalence of CrAg was 7.9% (95% CI, 4.7-12.4); 7.5% (12/159) in those with CD4 ≤100 cells/μL and 9.1% (5/55) in those with CD4 101 to 199 cells/μL. There were no statistically significant differences between sociodemographic, clinical or laboratory characteristics to predict CrAg positivity (p> 0.05). Conclusion: The prevalence of cryptococcal antigenemia in an HIV population with CD4 <200 cells/μL from midwest Brazil is high, above the cut-off point for the cost-effectiveness of CrAg screening. No clinical or laboratory factors could predict positivity, corroborating the need for universal screening for CrAg in severely immunosuppressed individuals infected with HIV in similar regions.